Upaya pencegahan Diabetes Melitus melalui edukasi kesehatan pada masyarakat Kampung Pelita Medika Buluh Cina - Miftah Azrin; Suyanto Suyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The incidence of Type 2 Diabetes Mellitus (DM) in rural areas shows an increasing number. For this reason, efforts to control diabetes need to be done through education to the public. Community service was conducted in the village of BuluhCina which is one of the fostered villages of Kampung Pelita Medika FK UNRI. Education is provided with Kukerta students through socialization of a healthy diet and checking blood sugar as a risk factor. Through this service, it is hoped that the community will have the awareness to control the risk factors for DM in BuluhCina village.